2014
DOI: 10.1371/journal.pone.0106482
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Glycoside Hydrolases for Debranched Xylan Degradation from Extremely Thermophilic Bacterium Caldicellulosiruptor lactoaceticus

Abstract: Caldicellulosiruptor lactoaceticus 6A, an anaerobic and extremely thermophilic bacterium, uses natural xylan as carbon source. The encoded genes of C. lactoaceticus 6A for glycoside hydrolase (GH) provide a platform for xylan degradation. The GH family 10 xylanase (Xyn10A) and GH67 α-glucuronidase (Agu67A) from C. lactoaceticus 6A were heterologously expressed, purified and characterized. Both Xyn10A and Agu67A are predicted as intracellular enzymes as no signal peptides identified. Xyn10A and Agu67A had molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 39 publications
(56 reference statements)
0
16
0
Order By: Relevance
“…These results indicate that CoGH1A has resistance to cations and additional cation is not necessary for activating the enzyme. The effects of cation on CoGH1A were similar to those on some other glycoside hydrolases from Caldicellulosiruptor species, such as the xylanase from C. kronotskyensis [ 22 ] and the xylanase and xylosidase from C. owensensis [ 12 ]. They were very different from the β-galactosidase produced by Lactobacillus delbrueckii [ 23 ].…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…These results indicate that CoGH1A has resistance to cations and additional cation is not necessary for activating the enzyme. The effects of cation on CoGH1A were similar to those on some other glycoside hydrolases from Caldicellulosiruptor species, such as the xylanase from C. kronotskyensis [ 22 ] and the xylanase and xylosidase from C. owensensis [ 12 ]. They were very different from the β-galactosidase produced by Lactobacillus delbrueckii [ 23 ].…”
Section: Resultsmentioning
confidence: 56%
“…Research efforts have recently focused on extremely thermophilic microorganisms for exploring novel cellulases and other GHs to improve the current situation [ 5 7 ], due to the advantages of these thermophilic enzymes, such as higher reaction velocity, excellent thermostability, and decreased risk of contamination [ 8 ]. Many thermophilic GHs, such as β- d -glucosidase [ 9 , 10 ], bifunctional cellulolytic enzyme (endo- and exoglucanases) [ 11 ], β- d -xylosidase [ 12 ], and β- d -galactosidase [ 3 , 13 ], have been cloned, heterologously expressed, and biochemically characterized for the purpose of uncovering the catalytic mechanism and evaluating the possibility of industrial applications. Among them, the genus Caldicellulosiruptor has recently attracted high interest for it can produce a diverse set of glycoside hydrolases (GHs) for deconstruction of lignocellulosic biomass [ 7 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…strain 41M-1 and Xyn10B (Protein Data Bank entry 2W5F; sequence identity, 29%) from Clostridium thermocellum, respectively, as the template. Quaternary structures of XynA and XynB were investigated using size exclusion chromatography with a Superdex 200 column (36,37). Blue dextran 2000 (2,000 kDa), ferritin (400 kDa), conalbumin (75 kDa), and ovalbumin (43 kDa) (all obtained from Sigma-Aldrich) were used as reference proteins.…”
Section: Methodsmentioning
confidence: 99%
“…It is worth noting that the hydrolysis of GH10-XA alone accumulated xylobiose, confirming that it was a bad substrate, and a third peak released later than 4-O-methyl-glucuronic acids and possibly corresponding to aldouronic acids. It is worth mentioning that GH10-XA and GH67-GC acted in synergy extremely well: if compared to the GH10 and GH67 enzymes from C. lactoaceticus [59], they produced the same amounts of reducing ends from beechwood xylan in 2 h vs 12 h and at much less enzyme concentrations (7-and 9-fold for GH10 and GH67 enzymes, respectively). On the basis of these encouraging results, and to improve the biotransformation and the synergy of GH10-XA and GH67-GC on these substrates, the high-xylose tolerant ␤-xylosidase from Thermotoga thermarum (GH3-XT) [42] was added to the enzymatic mixture.…”
Section: Resultsmentioning
confidence: 98%
“…This is, at the best of our knowledge, the only ␣-glucuronidase studied so far that is able to recognize as substrate both glucuronoxylan oligomers and 4Np-GlcUA. In fact, most of the GH67 ␣-glucuronidases are only active on 4-O-MeGlcA linked to the non-reducing end of xylo-oligomers [29,30,59] and only few studies demonstrated their high activity against longer polymeric substrates [32,33]. By contrast, the Agu4A ␣-glucuronidase from Thermotoga maritima from family GH4, which efficiently hydrolysed 4Np-GlcUA, was unable to recognize gluronoxylans as substrates [28,75].…”
Section: Resultsmentioning
confidence: 99%